The X[[S]]-Sub-Exact Sequence of Generalized Power Series Rings - Pardede, Wesly Agustinus; Faisol, Ahmad; Fitriani, Fitriani (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
Let  be a ring,  a strictly ordered monoid, and K, L, M are R-modules. Then, we can construct the Generalized Power Series Modules (GPSM) K[[S]], L[[S]], and M[[S]], which are the module over the Generalized Power Series Rings (GPSR) R[[S]]. In this paper, we investigate the property of X[[S]]-sub-exact sequence on GPSM L[[S]] over GPSR R[[S]].